2021
DOI: 10.1002/jgh3.12694
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of push and pull percutaneous endoscopic gastrostomy placements in 854 patients: A single‐center study

Abstract: Background and Aims Percutaneous endoscopic gastrostomy (PEG) is indicated for prolonged enteral nutrition. This study aimed to analyze the outcome and to identify potential risk factors for complications in PEG procedures. Methods A single‐center retrospective analysis of the performed PEG procedures during the period January 2010 till January 2020. Results A PEG placement procedure was performed in 854 patients (64.1% male) and was successful in 833 (97.5%). In total, 513 push (61.6%) and 320 pull (38.6%) PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…Our study's median PEG exchange duration was 9 months (0.5-6). Similarly, in a study by Bouchiba et al 16 the median follow-up was found to be 8.9 months. In our study, the median age was found to be 83 years (35-96) in the PEG exchange group, while Jung et al 2 reported the mean age of 77 years.…”
Section: Discussionmentioning
confidence: 65%
“…Our study's median PEG exchange duration was 9 months (0.5-6). Similarly, in a study by Bouchiba et al 16 the median follow-up was found to be 8.9 months. In our study, the median age was found to be 83 years (35-96) in the PEG exchange group, while Jung et al 2 reported the mean age of 77 years.…”
Section: Discussionmentioning
confidence: 65%
“…The most common types of complications include tube dislodgement, granulation tissue formation, local infection, minor bleeding, site leakage, and buried bumper. Significant hemorrhage and intestinal perforation are extremely rare complications [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 854 patients undergoing PEG placement (513 with push technique vs. 320 with pull technique), minor bleeding and tube dislodgement were more associated with push technique (6.9% vs. 2.1%, p = 0.002; 11.9% vs. 3.3%, p < 0.001), whereas buried bumper was more frequent in the pull technique (0.4% vs. 7.3%, p < 0.001) [ 5 ]. Major complications were exceptionally rare, and perforation occurred in three patients (all were in the pull technique group).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations